2019
DOI: 10.1002/lio2.291
|View full text |Cite
|
Sign up to set email alerts
|

The association between diabetes and olfactory impairment in adults: A systematic review and meta‐analysis

Abstract: Background Evidence suggests that olfactory impairment (OI) may be a degenerative neurologic complication of diabetes; however, the association is not yet well established. The objective of this work was to systematically review existing literature on the association between diabetes and OI in adults, with meta‐analysis of evaluable studies. Methods A literature search encompassing 358 abstracts from the last 75 years in PubMed, EMBASE, and Cochrane was performed. English‐language articles investigating adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…In our study, diabetes was associated with the development of GD and there was a trend of association with Sniffin'Stick test results. The association between diabetes and the development of OD is well known and supported by a recent meta-analysis [20]. Similar findings were observed in patients with GD, confirming the potential role of diabetes in the development of sense disorders [21].…”
Section: Discussionsupporting
confidence: 72%
“…In our study, diabetes was associated with the development of GD and there was a trend of association with Sniffin'Stick test results. The association between diabetes and the development of OD is well known and supported by a recent meta-analysis [20]. Similar findings were observed in patients with GD, confirming the potential role of diabetes in the development of sense disorders [21].…”
Section: Discussionsupporting
confidence: 72%
“…The Mona Lisa Study highlighted that obesity and increased blood glucose is directly linked with poor cognitive impairment and is already evident in middle-aged individuals 28 . Studies have suggested that olfaction disorders are basically due to neuro-degeneration and could occur as a diabetic complication 29 . Since impaired olfaction is an indicator of ageing in the elderly, but it was observed in the early ages in the current study due the presence of diabetes and obesity in the study participants.…”
Section: Resultsmentioning
confidence: 99%
“…The tests for evaluating the ability to identify odors have important cultural components [ 10 , 39 , 74 , 79 , 80 , 81 , 82 ]. The odorants of a well-validated identification test should be familiar to individuals from each country.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory tests are necessary tools for adequate assessment of olfactory function [ 1 ]. The use of olfactory assessment tests has become more relevant in recent years, due to clinical and research findings that indicate the existence of olfactory alterations derived from traumatic injuries as brain injury [ 2 , 3 ], in surgical or medical procedures for the treatment of some diseases such as larynx tumors requiring partial or total laryngectomy [ 4 ], treatment with radiotherapy [ 5 ], or pathologies with alterations of the sense of smell such as arterial hypertension [ 6 ], liver disease [ 7 , 8 ], diabetes mellitus [ 9 , 10 ], rhinitis, sinusitis [ 11 , 12 ], autoimmune diseases [ 13 , 14 ], inflammatory diseases [ 15 ], anxiety [ 16 , 17 ], major depression [ 18 , 19 , 20 , 21 ], schizophrenia [ 22 ], autism [ 23 ], and neurodegenerative diseases [ 24 , 25 ], such as frontotemporal dementia [ 26 , 27 , 28 ], amyotrophic lateral sclerosis [ 29 ], Parkinson’s disease [ 30 , 31 , 32 , 33 ], or Alzheimer’s disease [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%